Analisis Intra-Industry Trade Komoditas Tekstil dan Produk Tekstil (TPT) di Kawasan ASEAN Periode 2010-2023 - Wicaksana, Bagus; Ervani, Eva (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to analyze the intensity and determinants of intra-industry trade (IIT) textile and textile articles commodities between Indonesia and ASEAN countries during the 2010–2023 period. Utilizing panel data from ten ASEAN countries, the Grubel-Lloyd index, and a Fixed Effects model corrected with Generalized Least Squares (GLS), the study finds that Vietnam, Thailand, and Indonesia recorded the highest IIT levels. The Export Variety Index (EVI), industrial output, average GDP, per capita GDP differences, and R&D expenditure have a significant positive effect on IIT, while trade openness shows a significant negative effect. These findings highlight the critical role of product differentiation, economies of scale, and innovation in strengthening intra-industry trade. Policy implications include harmonizing industrial regulations and increasing investment in R&D to enhance the competitiveness of the ASEAN TTP sector.